Evolución del sistema general de riesgos profesionales, Colombia 1994 – 2004 (2009)
ABSTRACT: To analyze the regulation and ensuring the General System of Occupational Hazards in Colombia between 1994 and 2004. Methods: The evolution of regulation and its comparison with the principles of the Colombian social security was made by documentary analysis. A quantitative analysis determined the evolution of the insurance of companies and workers, by the legal nature of the Management Occupational Risks companies and social variables. Results: The structural and fundamental aspects are the most regulated. Some themes have great repetition. Promotion, prevention and decentralization are less visible. The efficiency and integrity principles are better developed. Solidarity, universality, unity and participation are under development. There is an increase of affiliated workers but a decrease of companies affiliated. The participation of the private companies increases and that of the public company decrease. The companies with more workers and more high quotes are affiliated to the assurances private companies. Discussion: The basic definitions are before the system. There are more regulations on the institutional arrangements and relationships between actors and less on conceptual and programmatic aspects in the promotion and prevention. Universality is threatened by economic and structural factors and by the same norms. The private participation is of great growth with a market approach toward the strongest sectors of the Colombian economy.